Systematics and molecular phylogenetics of Asian snail-eating snakes (Pareatidae) - Guo, Yuhong; Wu, Yunke; He, Shunping; Shi, Haitao; Zhao, Ermi (Zootaxa, 2011)
The taxonomy of the Asian snail-eating snakes (Pareatidae) is an ongoing controversy, partly because morphological characters do not yield consistent results across studies. We infer phylogenetic relationships within Pareatidae using ~ 2 kilobases of DNA sequences including two mitochondrial (cyt b and ND4) and one nuclear gene (c-mos). Results reveal four major lineages: Aplopeltura, Asthenodipsas, a clade formed by Pareas carinatus and P. nuchalis, and a clade comprising all other species of Pareas sampled in this study. Our data do not have enough signal to either support or reject a monophyletic Pareas. However, large molecular divergence (16.5%) is observed between the two major clades of Pareas, a level that is comparable to that between Pareas and Aplopeltura. Scale characters also suggest that P. carinatus and P. nuchalis are distinct from congeners, and future morphological and/or molecular studies might assess whether a distinct genus should be recognized. The molecular phylogeny further suggests a distant relationship between P. chinensis and P. formosensis and supports the validity of the former species.